THE EFFICIENCY OF PRODUCTION FACTORS ON AGRICULTURAL FARMS OF THE VISEGRAD GROUP - Agnieszka Cyburt; Agnieszka Gałecka (Polityki Europejskie, Finanse i Marketing)
The objective of the study was to determine the effectiveness of the use of production factors on farms of the Visegrad Group countries. The research covered farms participating in the European system for collecting accounting data from FADN (Farm Accountancy Data Network) farms. Under the main objective, an assessment was made of the productivity and profitability of land, labour and capital. The research period covered the years 2014-2017. Based on the analyses that was conducted, it was found that the most effective use of land resources was on farms in Hungary and Poland, and the least effective in Slovakia. Considering labour and capital productivity, the highest results were achieved by farms in the Czech Republic and Slovakia, while the lowest by Polish farms. On the other hand, Hungarian farms were characterized by the highest profitability of labour and return on assets, where the analysed indicators were higher than the EU average.